2010
DOI: 10.1016/j.jtcvs.2009.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Early and midterm results of thoracic endovascular aortic repair of chronic type B aortic dissection

Abstract: Early and midterm results show that thoracic endovascular aortic repair was effective in the treatment of chronic type B aortic dissection. Endoleak was the main cause of death during follow-up. With increased surgical experience and refinement of the stent graft, results are likely to improve in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 20 publications
2
57
0
1
Order By: Relevance
“…In the case of replacement of the descending thoracic aorta, the intercostal arteries were usually not reconstructed, except in patients with Marfan syndrome. However, in the case of replacement of the thoracoabdominal aorta, [2][3] pairs of intercostal arteries between Th8 and L3 were reconstructed. The flow rate in the lower body was approximately 2.0 l·min -1 ·m 2 during distal clamping.…”
Section: Operative Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of replacement of the descending thoracic aorta, the intercostal arteries were usually not reconstructed, except in patients with Marfan syndrome. However, in the case of replacement of the thoracoabdominal aorta, [2][3] pairs of intercostal arteries between Th8 and L3 were reconstructed. The flow rate in the lower body was approximately 2.0 l·min -1 ·m 2 during distal clamping.…”
Section: Operative Techniquesmentioning
confidence: 99%
“…Although early and midterm results show that endovascular treatment is effective, new intimal tears occur at the end of the stent graft because of narrowness and limited flexibility of the true lumen; these tears lead to re-intervention or rupture during the follow-up period. [1][2][3] Recently, Xu et al reported that to avoid a proximal endoleak, the distance between the entry tear and opening of the left subclavian artery should be more than 10 mm. Furthermore, to avoid a distal endoleak, they recommended the use of a tapered stent graft.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, normal aortic diameter rarely exceeds 40 mm and gradually tapers downstream, but in aortic dissection, larger taper becomes common from the left subclavian artery to downstream of the true lumen of the descending aorta. [10][11][12] The stent grafts used in aortic aneurysm repair are usually tubular or small taper designed with rigid length, like 160 mm, 180 mm, and 200 mm. In aortic dissection repair, the changeable and taper morphology of true lumens calls for large-taper stents with flexible length for better aorta remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese group recently reported on 84 patients undergoing TEVAR for chronic type B dissection, 16 but they did not report the indication for repair in their cohort, and their practice is "to treat all patients with chronic type B dissection with a patent false lumen." That practice is in stark contrast to ours, which is to treat only symptomatic or aneurysmal type B dissections.…”
Section: Discussionmentioning
confidence: 99%